The Efficacy of Biofeedback Therapy for the Treatment of Fecal Incontinence After Soave Procedure in Children for Hirschsprung's Disease - Yuan, Yuhang; Xu, Mengyao; Yang, Heying; Sun, Beibei; Li, Yanan; Zhang, Ning; Wang, Guantao; Su, Fan (Frontiers in Pediatrics, 2021)
Introduction: Hirschsprung's disease is a common digestive tract malformation in children, Soave procedure is one of the classic surgical methods for HD. Fecal incontinence is a common postoperative complications that can cause significant distress to the patients and their family, while biofeedback therapy (BFT) can be an effective treatment for managing it. The main objective of this study is to evaluate the effificacy of BFT for the treatment of postoperative fecal incontinence in children for Hirschsprung's disease (HD). Methods: A total of 46 children received Soave procedure for HD who suffered postoperative fecal incontinence were enrolled in the present study, who received BFT at our institution from March 2016 until August 2020, included 38 males and 8 females (mean age, 8.1 years old from 3.7 to 14) . BFT was performed by employing visual and verbal feedback techniques using the biofeedback instrument. The clinical outcome was evaluated by Kelly’s clinical score(KCS). Defecation questionnaires and anorectal manometry were completed pretreatment and after 3 or 6 or 9 sessions. Results: Followed up from 6 months to 4 years, the symptoms of fecal incontinence disappeared completely in 39 (84.78%) patients. And 7 (15.22%) cases still suffered fecal incontinence mildly. The AMCP after 3 and 6 sessions in poor group was significantly increased compared with that before treatment [(109.68±32.27)mmHg vs (95.02±31.18)mmHg vs (63.39±38.22)mmHg, P＜0.05]. The ALCT and ARP showed the same trend, while the RRP after 3 and 6 sessions were not significantly(P＞0.05). The mean (±SD) score of KCS increased from 3.1±0.32 to 4.9 ± 1.10 in fair group, while it increased from 1.72 ± 0.45 to 4.83 ± 0.85 in poor group after 6 sessions (P <0.05). Conclusion: Biofeedback therapy is a safe and effective treatment of fecal incontinence after Soave procedure of children for Hirschsprung's disease. It is beneficial to design the individualized treatment programs for the children with varying degrees of fecal incontinence.